Psychosocial Safety Climate and Job Performance Among Penang Island Hoteliers: The Mediating Roles of Challenge Demands and Hindrance Demands - Teoh, Kok Ban (Animo Repository, 2021)
Due to the COVID-19 pandemic, Penang Island hoteliers cannot perform their job to meet the customers’ expectations due to their high job demands. Hence, this paper intends to examine the predictors of job performance among Penang Island hoteliers. Furthermore, the paper intends to investigate the potential role of challenge demands and hindrance demands as mediating variables. A total of 107 hoteliers from Penang Island hotels participated in the study. The study results showed that psychosocial safety climate and challenge demands possess a significant positive relationship with job performance, whereas psychosocial safety climate has a significant negative relationship with hindrance demands. Moreover, hindrance demands were found to serve as a significant mediator on the relationship between psychosocial safety climate and job performance. The study’s findings are to help practitioners who wish to increase job performance among hoteliers in Malaysia.